Desain Sensor Tingkat Kekeruhan Air Menggunakan Bahan Fiber Optik - Silviana Dewi Masitoh; Yoyok Heru Prasetyo Isnomo; Lis Diana Mustafa (Politeknik Negeri Malang, 2021)
The importance of knowing the level of turbidity of water, especially in the activity of using drinking water in the form of clean water, requires a tool to be used to measure the level of turbidity of water. The use of optical fiber to determine the level of turbidity of water from the value of power loss is expected to be a solution to determine the level of turbidity of water before use. The research was conducted by measuring the value of power loss at the two ends of singlemode and multimode optical fiber connected to a fiber coupler, then measured using a Handheld Light Source and Optical Power Meter. The fiber coupler is modified by giving a 1mm hole at the center point to pass the tested water. Measurements were carried out with the condition of two optical ends without distance, the optical end was spaced 1mm apart, the optical end was spaced 1mm through clear water and water with a clouding agent in the form of ink. The largest measurement loss was obtained in singlemode optical fiber with a yellow color effect of 1.9dB. In multimode optical fiber, the yellow color cloud is 2.81dB. The results of the graph and calculation of power loss show the effect of adding an ink clouding agent to the measured power in the OPM. Based on the measurement results of changes in power loss that are not constant for each addition of 5 ml of turbidity, the sensor designed has low sensitivity.